IMPLEMENTASI ASIMILASI KERJA SOSIAL NARAPIDANA KORUPSI DI LEMBAGA SOSIAL SEBAGAI UPAYA REINTEGRASI SOSIAL - Junhaidel Samosir; Alvi Syahrin; Mahmud Mulyadi; Jusmadi Sikumbang (Universitas Sumatera Utara, 2017)
ABSTRACT It is recommended that reconstruction of legal concept and provisions which regulate the assimilation for corrupt prisoners and its implementing regulation should be done. In this case, 1) the Government Regulation No. 99/2012 on the Second Amendment of the Government Regulation No 32 on the Requirement and Procedure of the Implementation of Prisoners’ Rights should be revoked, 2) Adjustment to the corrupt prisoners’ level of education and professionalism should be in accordance with the purpose of establishing social institution with its statutes so that assimilation is not formal as the requirement for conditional acquittal. The social institution as the place for the assimilation should match with what the prisoners had corrupted so that they will realize the impact of what they had done, and 3) the capacity of the wardens of Medan Penitentiary for corrupt prisoners should be improved, and the Penitentiary management of Medan should collaborate with all social institutions in its vicinity so that the corrupt prisoners will not be difficult to find the places for doing their social work assimilation. Keywords: Assimilation, Social Work, Corrupt Prisoner, Social Reintegration